+0  
 
0
50
2
avatar

Let p and q be the two distinct solutions to the equation x^2 - 2x - 3 = 0. What is (p+1)(p+1)?

 Mar 18, 2021
 #1
avatar+118015 
+1

x^2 - 2x  - 3  =  0

( x - 3) ( x + 1)  = 0

Setting  each factor  to 0  and  solving for x  we get   x  = 3  and  x = -1

 

If  p   =  -1    then    ( -1 + 1) ( -1 + 1)  = (0) * (0)  =   0

If  p =  3   then ( 3 + 1) (3 + 1) =  (4) * (4)  =  16

 

 

cool cool cool

 Mar 18, 2021
 #2
avatar
0

Tysm!

Guest Mar 18, 2021

55 Online Users

avatar
avatar
avatar
avatar
avatar
avatar